Quality of life of mothers of children with congenital syndrome affected by Zika virus - Lobao de Araujo Costa, Paulo Rogerio; Arruda Aragao, Francisca Bruna; Serra, Jacira do Nascimento; Andrade, Marcelo Sousa; Reis, Andrea Dias [UNESP]; Soares Brandao Nascimento, Maria do Desterro (Soc Pediatria Sao Paulo, 2021)
Objective: To investigate how mothers of children with congenital syndrome (microcephaly) associated with Zika virus perceive their quality of life. Methods: This is a qualitative study carried out in two stages: at the Maternal and Child University Hospital and at Casa de Apoio Ninar through semi-structured interviews with mothers of children with congenital syndrome associated with Zika virus. Ten women comprised the sample. Results: In line with the critical discourse analysis, four categories emerged based on Fairclough's 2008 assumptions: Quality of Life and Health - quality of life perception associated with the broad meaning of the term health; Quality of Life and Health Care Systems - characterized by care instability and fragmentation; Quality of Life and Free Time - lack of free time for activities of daily living and leisure; Quality of Life and Future Perspectives - lack of future perspective, considering that most participants had to stop working and studying to take care of their children. Conclusions: Mothers of children with congenital syndrome associated with Zika virus are devoted to their children's care. Their lack of prospects was considered a consequence of the lack of time for activities of daily living and leisure.
Keywords: Quality of life; Microcephaly; Zika virus